STUDI POPULASI DAN PERILAKU TARSIUS (Tarsius spectrum) DAN PENGEMBANGANNYA SEBAGAI OBYEK ATRAKSI SAFARI MALAM DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG SULAWESI SELATAN - Rika S. Santoso (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
Tarsier is the smallest primates in Southeast Asia, having large eyes, head flexible and can rotate 180 degrees and unique behavior is the main attraction. The existence of Tarsius in Indonesia is very important role to people's lives as pest controllers because of its main food is insects. But its existence is now in danger. The purpose of this study is to give information about the population, behavior and distribution Tarsier (Tarsius spectrum) in Bantimurung Bulusaraung National Park, Tarsius spectrum provides information that is currently still less and recommend the observations interpretation of Tarsius spectrum. Research conducted in the forest block of Bantimurung, Karaenta, Pattunuang, Pute and Pappang in Bantimurung Bulusaraung National Park, Regency of Maros -Pangkep, South Sulawesi Province. On August 10 to 20, 2007. Observation method of population, behavior and distribution of Tarsius spectrum is line transect method, and Squares method. Observations done in the morning (at 5:30 a.m. to 8:00 pm), afternoon (4:00 p.m. to 18:00 pm GMT) and nighttime (20:00 to 23:00 o'clock). The main habitats of Tarsius spectrum in Bantimurung Bulusaraung National Park is riparian and bamboo groves. The population of Tarsius spectrum is found which is about 10 groups in the forest block of Pute, Pappang and Pattunuang. Behavior of the dominant encounter is voiced. Encounter high intensity in the Bantimurung Bulusaraung National Park is one opportunity for development become tourist attractions of wildlife observation with the main object Tarsier. Pathways that can be used for observation is all Bisseang Labboro until Pattunuang Cave. Keywords: Tarsius spectrum, ecotourism, Bantimurung Bulusaraung.